Pengaruh Model Project Based Learning Berbasis Media Manipulatif Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Yana Nababan, Lina; Khairani Hasibuan, Eka; Ammamiarihta, Ammamiarihta (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
This study aims to determine the effect of the Project Based Learning (PjBL) model based on manipulative media on students’ mathematical problem-solving abilities in the Pythagorean Theorem topic. This research employed a quasi-experimental method with a posttest-only control group design. The subjects were eighth-grade students of MTs Swasta Laboratorium IKIP Al-Wasliyah Medan, consisting of two classes: an experimental class and a control class, each with 26 students. The experimental class received instruction using the PjBL model based on manipulative media, while the control class was taught through a conventional learning model. The research instrument was a mathematical problem-solving test. The results showed that the experimental class achieved an average posttest score of 81.85, while the control class scored 55,19. The Independent Sample t-Test analysis revealed that the calculated t-value (10.722) was higher than the critical t-value (2.009) with a significance level of 0.000 < 0.05, indicating that H₀ was rejected and H₁ accepted. Therefore, it can be concluded that the implementation of the Project Based Learning model based on manipulative media significantly influences students’ mathematical problem-solving abilities